Analysis of cable effect on dynamic motion of an underwater vehicle for welding of reaction pool. (November 2019) - Li, Zhandong; Tao, Jianguo; Sun, Hao; Luo, Yang; Li, Jingkui; Deng, Zongquan
Remotely operated vehicle is a reliable tool in an emergency rescue and routing inspection of a reactor pool. In practice, a cable has been considered as an important part of a vehicle system (i.e. winch, vehicle, and cable) to evaluate and predict the mechanical characteristics, and this article presents a study on a dynamic mechanism modeling of a cable partially in water and air based on an omnidirectional motion, and a numerical simulation is employed. In this work, we programmed the model governed by a partial differential equation set, at the discrete time node which was transformed into an ordinary differential equation set regarded as an initial value problem. The dynamic mechanical characteristics of the lower endpoint (i.e. a connection point between vehicle and cable) and the upper endpoint (i.e. a connection point between cable and winch) were, respectively, quantified with acceleration and a compounded motion including a uniform and rolling motion. A dynamic-state mechanism test was carried out to verify an authenticity of the three-dimensional mechanical model and numerical solution in a circulating tank. The results demonstrated that the presented method was used to evaluate the dynamic mechanism, and held a potential to improve a vehicle design and control strategy.